2023
DOI: 10.1002/bab.2445
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, enzyme inhibition, and molecular docking studies of a novel chalcone series bearing benzothiazole scaffold

Abstract: This study reports the facile synthesis of a novel series of benzothiazole‐chalcones, in addition to their inhibitory profile on important metabolic enzymes including human carbonic anhydrases (hCA‐I, hCA‐II) and paraoxonase (PON‐1). The inhibition parameters, IC50 (concentration for 50% inhibition) and Ki (dissociation constant) values, toward the title enzymes were determined for the studied compounds. As a result, IC50 values of hydratase activity were in the range 4.15–5.47 and 2.56–4.58 μM for hCA‐I and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Based on previously published research, the studied compounds (3a-h) underwent calculations to determine their HOMO (highest occupied molecular orbital) and LUMO (lowest unoccupied molecular orbital) energies, with the lowest values being chosen along with various quantum chemical parameters which were determined accordingly using the proper formula and methodology [46][47][48][49]52]. Tables 2 and 3 present some of the obtained results.…”
Section: B32 Molecular Descriptors Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previously published research, the studied compounds (3a-h) underwent calculations to determine their HOMO (highest occupied molecular orbital) and LUMO (lowest unoccupied molecular orbital) energies, with the lowest values being chosen along with various quantum chemical parameters which were determined accordingly using the proper formula and methodology [46][47][48][49]52]. Tables 2 and 3 present some of the obtained results.…”
Section: B32 Molecular Descriptors Evaluationmentioning
confidence: 99%
“…These calculations provide valuable insights into the electronic structure, stability, and reactivity of the molecules, contributing to a better understanding of their properties and potential applications. Quantum chemical parameters, such as EHOMO, ELUMO, ΔE (the energy difference between HOMO and LUMO), hardness, electronegativity, chemical potential, global electrophilicity, nucleophilicity, global softness, dipole moments, ionization energies, and electron affinities, can all be considered when evaluating the biological potential of a molecule [52]. One can observe by looking at the given Table 1 which contains some calculated parameters for the studied compounds along with the data of Figure 6 that 3a-h compounds have similar or near energy band gap energy difference (ΔE) in gas phase.…”
Section: Theoretical Studiesmentioning
confidence: 99%
“…Newly synthesized compounds were screened for their inhibitory activity against CA-II and it was observed that compound 264 found to show good activity [49] (Scheme 30). Density functional theory (DFT) studies showed that newly synthesized compounds fit into the active site of enzymes which was responsible for their bioactivity [50] (Scheme 31). Initially, bromine substituted salicylic acid 274 was reacted with substituted boronic acids in presence of K 2 CO 3 , pd(pph 3 ) 4 and toluene/H 2 O at 90°C for 24 h to prepare corresponding aldehyde 275(a-j) followed by reaction with ClSO 2 NH 2 in presence of DMA at r.t. for 24 h to obtain their corresponding 276(a-j) and 277(a-j).…”
Section: S C H E M E 24 Synthesis Of 216(a-e)mentioning
confidence: 99%
“…Density functional theory (DFT) studies showed that newly synthesized compounds fit into the active site of enzymes which was responsible for their bioactivity [ 50 ] (Scheme 31).…”
Section: Chemistry Of Heterocycles As Ca Inhibitorsmentioning
confidence: 99%